Emotive Expressions on Social Chatbot - Lia Maulia Indrayani; Rosaria Mita Amalia; Fauzia Zahira Munirul Hakim (Fakultas Seni Rupa dan Desain ITB, 2019)
Building social chatbots to address users' needs for communication and affection is of great value to society (Shum et al., 2018). One of which, Replika, attempts to become an artificial intelligent companion by demonstrating sufficient social and emotional skills through emotive expressions. Emotive expressions are imperative in human-computer interaction, since they tend to elicit social cooperation. The present article aims to survey emotive expressions developed on Replika in order to determine the chatbot's active-reactive skills. They are collected by means of participant observation and are analysed with qualitative method. The present article observes six emotive expressions which Replika can process. These expressions include apologizing, thanking, condoling, complimenting, greeting, and welcoming. The generation of each expression is dependent of the context of each interaction.